Gravity or turbulence? – III. Evidence of pure thermal Jeans fragmentation at ∼0.1 pc scale. Issue 4 (10th September 2015) - Palau, Aina; Ballesteros-Paredes, Javier; Vázquez-Semadeni, Enrique; Sánchez-Monge, Álvaro; Estalella, Robert; Fall, S. Michael; Zapata, Luis A.; Camacho, Vianey; Gómez, Laura; Naranjo-Romero, Raúl; Busquet, Gemma; Fontani, Francesco
Abstract: We combine previously published interferometric and single-dish data of relatively nearby massive dense cores that are actively forming stars to test whether their 'fragmentation level' is controlled by turbulent or thermal support. We find no clear correlation between the fragmentation level and velocity dispersion, nor between the observed number of fragments and the number of fragments expected when the gravitationally unstable mass is calculated including various prescriptions for 'turbulent support'. On the other hand, the best correlation is found for the case of pure thermal Jeans fragmentation, for which we infer a core formation efficiency around 13 per cent, consistent with previous works. We conclude that the dominant factor determining the fragmentation level of star-forming massive dense cores at 0.1 pc scale seems to be thermal Jeans fragmentation.